Fox evil - Walters, Minette, 1949- (Pan Books, 2003)
Friendless and alone after his wife dies under suspicious circumstances, Colonel James Lockyer-Fox searches desperately for the illegitimate grand-daughter who could be the only answer to the problems plaguing his name and his life.